Effect of very low-intensity resistance exercise with slow movement and tonic force generation on post-exercise inhibitory control. Issue 2 (February 2021) - Dora, Kento; Suga, Tadashi; Tomoo, Keigo; Sugimoto, Takeshi; Mok, Ernest; Tsukamoto, Hayato; Takada, Shingo; Hashimoto, Takeshi; Isaka, Tadao
Abstract: Background: The extremely low loads (e.g., <30% of one-repetition maximum) involved in performing resistance exercise are effective in preventing musculoskeletal injury and enhancing exercise adherence in various populations, especially older individuals and patients with chronic diseases. Nevertheless, long-term intervention using this type of protocol is known to have little effects on muscle size and strength adaptations. Despite this knowledge, very low-intensity resistance exercise (VLRE) with slow movement and tonic force generation (ST) significantly increases muscle size and strength. To further explore efficacy of ST-VLRE in the clinical setting, this study examined the effect of ST-VLRE on post-exercise inhibitory control (IC). Methods: Twenty healthy, young males (age: 21 ± 0 years, body height: 173.4 ± 1.2 cm, body weight: 67.4 ± 2.2 kg) performed both ST-VLRE and normal VLRE in a crossover design. The load for both protocols was set at 30% of one-repetition maximum. Both protocols were programmed with bilateral knee extension for six sets with ten repetitions per set. The ST-VLRE and VLRE were performed with slow (3-sec concentric, 3-sec eccentric, and 1-sec isometric actions with no rest between each repetition) and normal contractile speeds (1-sec concentric and 1-sec eccentric actions and 1-sec rests between each repetition), respectively. IC was assessed using the color-word Stroop task at six time points: baseline, pre-exercise, immediate post-exercise, and every 10 min during the 30-min post-exercise recovery period. Results: The reverse-Stroop interference score, a parameter of IC, significantly decreased immediately after both ST-VLRE and VLRE compared to that before each exercise (decreasing rate >32 and 25%, respectively, vs. baseline and/or pre-exercise for both protocols; all P s < 0.05). The improved IC following ST-VLRE, but not following VLRE, remained significant until the 20-min post-exercise recovery period (decreasing rate >48% vs. baseline and pre-exercise; both P s < 0.001). The degree of post-exercise IC improvements was significantly higher for ST-VLRE than for VLRE ( P = 0.010 for condition × time interaction effect). Conclusions: These findings suggest that ST-VLRE can improve post-exercise IC effectively. Therefore, ST-VLRE may be an effective resistance exercise protocol for improving cognitive function. Abstract : Cognitive function; Brain health; Lactate; Electromyographic activity; Arousal